PENGARUH CASH HOLDING DAN TANGIBILITY TERHADAP FIRM PERFORMANCE DENGAN HUTANG SEBAGAI MODERASI - Lieta Tandra, F.X.Kurniawan Tjakrawala (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This study was conducted to test and determine whether the Cash Holding and Tangibility variables, if added by the moderating variable Debt, can have an effect that strengthens or weakens Firm Performance. The population in this study are Real Estate Companies listed on the Indonesia Stock Exchange for the period of 2016-2018. This study used a sample of 47 company samples and used the Eviews 10.0 program as a data processing program. The results showed that the debt variable does not affect Cash Holding on Firm Performance, while the debt variable weakens the effect of Tangibility on Firm Performance.